Why Do Employees Leave Organisations? Have a Critical Look at your Recognition System - Islam, Rafikul (IIUM Journal of Case Studies in Management, 2019)
Recognition of employees’ achievements is one of the most important factors to motivate employees. Employees who perform exceptionally well, expect that their contributions will be recognized or they will be appreciated by the top management. Over the decades (or perhaps centuries) the reward and recognition system has been adopted by numerous organisations – private or public. There are myriad ways by which employees can be appreciated. Further, one special type of reward may not motivate equally everyone. One person’s reward may be perceived by another person as punishment. The present case illustrates a classic example of how an organisation loses a bright employee due to absence of a proper recognition system.